Sumbangan Pemikiran Etika Global Hans Kung Demi Terwujudnya Perdamaian Dan Relevansinya Bagi Indonesia (Critical Discourse Analysis Terhadap Naskah Etika Global) - Darmin Suhanda (IAKN Tarutung, 2021)
ABSTRACTThe purpose of this research is to describe Hans Kung Global Ethics, to describe the contribution of Hans Kung Global Ethics for the realization of peace and the interesting relevance of Hans Kung Global Ethics for peace in Indonesia. The background of the research carried out by the researcher is to find the meaning of an unconditional ethical foundation in Hans Kung's discourse in the Global Ethics Manuscript so that its relevance to peace in Indonesia has recently been struggling in religious conflicts.The research method used by researchers in this study is to use a qualitative approach with Fairclough's Critical Discourse Analysis method. The method of critical discourse analysis is reading / interpreting the intrinsic and extrinsic meaning sentence by sentence of the Hans Kung Global Ethics manuscript by paying attention to the relationship between parts and sentences and analyzing the context and history.The results of the research analysis of the Global Ethics text are that the author finds the ethical foundation of each religion that is determined by religions as a consensus. Global ethics cannot necessarily be used to solve all problems, but this foundation can be used as a basis for action by religious communities in the midst of the world and especially in the midst of Indonesia. Conflicts that destroy the image of peace in Indonesia must be the reason that it is a necessity of the religious community, and the result is suffering. Religious people who are conflicted because of differences in dogmas realize that this weak point is not something that must be debated and contested, if one another still considers the presence of differences as taboo, then the result will be conflict between religious communities. There can be no survival without a basic ethic, and there can be no peace in Indonesia without peace between religions. And there can be no religious peace without dialogue between religions.